2022
DOI: 10.1002/pssa.202100747
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum‐Induced Morphotropic Phase Boundary in BiFeO3–BaTiO3‐Based Lead‐Free Piezoelectric Ceramics

Abstract: La x Fe 0.98 Ga 0.02 O 3 -0.29BaTiO 3 þ 0.1wt%MnO 2 ceramics are fabricated via a traditional solid-state reaction route. Rietveld refinement analysis of X-ray diffraction data shows that all the studied ceramics consist of rhombohedral and tetragonal phases. The La-free samples are dominated by rhombohedral phase, the proportion of which, however, gradually decreases with the addition of La. And in 0.005 ≤ x ≤ 0.02, the ceramics have approximately equal proportions of rhombohedral and tetragonal phases, showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The increase at x = 0.15 is due to nearly equal proportions of R and T phases, appears at this concentration as it has more spontaneous polarization vectors from both the phases which disturbs after further increment of Sm concentration as in the case of La modified BFO-BTO ceramics [43]. Specifically, it is observed that high T C of 550 °C is achieved for x  0.025 of the composite ceramics.…”
Section: Surface Topographymentioning
confidence: 78%
“…The increase at x = 0.15 is due to nearly equal proportions of R and T phases, appears at this concentration as it has more spontaneous polarization vectors from both the phases which disturbs after further increment of Sm concentration as in the case of La modified BFO-BTO ceramics [43]. Specifically, it is observed that high T C of 550 °C is achieved for x  0.025 of the composite ceramics.…”
Section: Surface Topographymentioning
confidence: 78%